From Comfort to Conflict: Hotel Responsibilities and Water Rights in Yogyakarta - Yesaya Sandang (Human Rights in the Global South (HRGS), 2024)
This article provides a socio-legal analysis of hotel responsibilities in upholding the human right to water, with a focus on Yogyakarta, Indonesia. It explores the obligations of hotels beyond legal compliance, examining relevant regulations and integrating primary data from interviews and observations of government agencies. The study identifies a significant disparity between statutory laws and their practical implementation, revealing tangible societal impacts. Furthermore, it highlights a gap between sustainable tourism discourse and the application of sustainable practices in hotel operations. Constraints and challenges within the existing legal framework for sustainable tourism are critically analysed, emphasising the need for reform. This research underscores the urgency of integrating water governance into the broader agenda of sustainable tourism, aligning with government priorities on tourism development. Methodologically, the study employs a qualitative approach, utilising socio-legal analysis to connect regulatory frameworks with real-world practices. By advancing discussions on sustainable practices in the hospitality sector, this study contributes significantly to the broader discourse on aligning tourism development with human rights and environmental sustainability. It fills a gap in the literature by systematically connecting water governance, human rights, and tourism regulation within a single analytical framework. Its urgency lies in addressing the escalating water resource challenges amidst tourism growth. The study concludes by emphasising the need for policy adjustments to address the disconnect between legislative frameworks and practical implementation, providing actionable insights for policymakers and stakeholders. Its novelty lies in reframing water governance in hotels as a central issue within sustainable tourism, rather than a peripheral or niche concern.